SECONDARY PREVENTION OF CARDIOVASCULAR DISEASES AMONG PATIENTS OF DIFFERENT AGE GROUPS WITH A HISTORY OF MYOCARDIAL INFARCTION BY THE EXAMPLE OF OUTPATIENT CARDIOLOGY INSTITUTION - S. B. Fitilev; D. A. Dimitrova; I. I. Shkrebneva; A. V. Vozzhaev (Столичная издательская компания, 2017)
Aim. To study secondary prevention of cardiovascular diseases among patients of different age groups with a history of myocardial infarction by the example of outpatient cardiology institution.Material and methods. Retrospective pharmacoepidemiological study was conducted by analyzing the medical records of 825 patients with a history of myocardial infarction, who visited the outpatient cardiology institution for the first time in 2011. Patients were divided into two groups according to their age: younger than 60 years (n=308), and 60 years and older (n=517).Results. The population of elderly patients was more severe: significantly more often patients had disability and comorbidities. The prevalence of the main modifiable risk factors could not be assessed fully due to the lack of information in patients' medical records. Elderly patients were significantly less likely to receive β-blockers (80.3%) and statins (63.8%). No significant differences were found in daily doses of the main prescribed preventive drugs between two groups.Conclusion. Secondary prevention of cardiovascular diseases among patients of different age groups could not be considered proper, as there is low level of attention to the modifiable risk factors and recommendation on their correction. A tendency to under-prescription of angiotensin converting enzyme inhibitors was revealed, as well as significantly lower number of recommendations for taking statins and β-adrenoblockers in the group of elderly patients.